Conspecific brood parasitism in waterfowl and cues parasites use - Pöysä, Hannu; Eadie, John M.; Lyon, Bruce E. (Wildfowl, 2014)
Conspecific brood parasitism (CBP) occurs in various insects, fishes and birds, but it is disproportionately common in waterfowl (Anatidae). Studies of CBP in Anatids therefore have helped to develop a fundamental conceptual framework with which to explain this intriguing behaviour. Yom-Tov (1980) first drew attention to CBP, and Andersson and Eriksson (1982) also hinted at the fascinating behavioural, ecological and evolutionary aspects of CBP in waterfowl. Several reviews followed these early papers, but much has been learned more recently about CBP in waterfowl. Here we aim to review the traditional conceptual framework of CBP in waterfowl and to consider empirical studies that have attempted to test related hypotheses. The survey provided support for the hypotheses that CBP allows some females to reproduce when not otherwise possible, whereas other females use parasitic egglaying as a way to enhance their fecundity. A recently developed framework that considers CBP as part of a flexible life-history strategy could provide a useful direction for future studies of CBP. A second aim of this review is to consider the use of cues by conspecific brood parasites seeking suitable places to lay eggs parasitically. Recent studies have revealed remarkable cognitive abilities in parasitic females, but the actual mechanisms remain unknown. Clearly, breeding females are sensitive to cues such as nest site security, patterns of previous nest use or success, clutch size, and perhaps even the degree of kinship between hosts and other parasites. Indeed, additional investigations of CBP are needed to provide a better understanding of the processes and patterns of this avian reproductive strategy.